INTERNAL COMMUNICATION CHALLENGES IN 21ST CENTURY ORGANIZATION Leadership perspective - Zaumane, Ieva (IJRDO - Journal of Business Management, 2018)
communication and employee engagement on achievement of business goals. The literature review will offer critically analytical view on the latest publications and researches about the role of internal communication and employee engagement in organizational performance. In addition, author will come forward with results of the pilot survey about relationship between employees and employers in organizations in Latvia.The author used quantitative and qualitative research methods including “snow ball” method in conducting survey and literature review on internal communication and its challenges in 21st century organization. In this article, the author provides the proof to the assumption that internal communication is a complex concept challenging the organization’s management, employee engagement and productivity and organizations performance. Also, pilot survey presents, that employees in organizations in Latvia feel more like tools rather than, valuable resource. Particular finding asks for further research regarding its impact on internal communication and engagement.